Early postpartum discharge: maternal depression, breastfeeding habits and different follow‐up strategies. Issue 1 (15th August 2018) - Verpe, Hege; Kjellevold, Marian; Moe, Vibeke; Smith, Lars; Vannebo, Unni T.; Stormark, Kjell Morten; Søvik, Margaret Ljosnes; Skotheim, Siv
Abstract : Background: In most maternity wards in Norway, early discharge (<48 hour) is the norm. To monitor newborns' and women's health during the first week after delivery, most maternity wards offer early check‐ups, where families return to the hospital (standard care). However, a few municipalities offer home visits by midwives (domiciliary care) to ensure seamless services for the family. Aim: The primary aim of this study was to explore whether different follow‐up strategies were differently associated with maternal depression and breastfeeding habits, 6 weeks and 6 months postpartum. The secondary aim was to investigate whether families at risk of postpartum depression were included in the home visiting programme in the municipality that offered both follow‐up strategies. Method: This study draws on data from the 'Little in Norway' (LIN) study, which followed families from pregnancy until the child was 18 months. This study used data from two different well‐baby clinics in two municipalities, where one offered standard care (n = 95) and the other domiciliary (n = 64) and standard care (n = 17). The Edinburg Postnatal Depression Scale (EPDS) was used to measure maternal depression. Breastfeeding habits were measured using a self‐report questionnaire. The Life Stress subscale of the Parenting Stress Index (PSI) was used to identify women at risk of postpartum depression. Results: There were no differences in maternal depressive symptoms or breastfeeding habits at neither 6 weeks nor 6 months postpartum between women who received standard or domiciliary care in the two municipalities. Within the municipality that offered both follow‐up strategies, a higher number of women scoring high on prenatal life stress were included in domiciliary – compared to standard care. Conclusion: Differential follow‐up strategies in the first week after birth did not impact on maternal depression or breastfeeding habits. However, domiciliary care seems to be regarded as supportive and nonstigmatising for women at risk of postpartum depression.